Dampak Konten Vidio Animasi pada Peningkatan Pemahaman Siswa terhadap Pembelajaran IPS yang Terintegrasi di Pendidikan Dasar - Muthia Khairani; Eka Saskiawati; Oman Farhurohman (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of documenting the findings is to evaluate the extent to which the use of audio-visual media can implement learners' academic performance in Social Studies subjects at the primary school level. This research has been conducted using a qualitative method complemented by a descriptive approach, relying on data obtained from a literature review. Data sources include relevant scientific articles, books and journals that support previous findings and are in line with the main topic of this study. The research shows that the use of audiovisual media has a significant impact on improving students' learning rubric in social studies subjects. Audio-visual media proved effective because it was able to encourage active student involvement through activities such as asking questions, discussing, and responding to the material presented. In this case, it was due to the efficient presentation of the video that was able to keep learners' attention and reduce the risk of boredom. Thus, this engagement contributes to their improved academic performance. The integration of audio-visual media in social studies learning in elementary schools has a major positive impact on students' academic achievement and learning motivation.